PENENTUAN KONSENTRASI KHLOROFIL-Î± SEBAGAI INDIKATOR KUALITAS PERAIRAN WADUK SAGULING - Komarawidjaja, Wage (Jurnal Hidrosfir Indonesia, 2008)
Saguling reservoir is one of reservoir located in West Java Province. This reservoir primarily was planned for single purpose to generate the electricity. Water quality in this reservoir is depends on the water quality of Citarum River which have face significant change because of the increased of land use along Citarum River basin. Parameter that tends to increased as well as measured at Saguling reservoir in this study is pH, turbidity and Chlorophyll- . These results are higher than the permissible limit (PP 82/2001). Its mean that Saguling reservoir water quality is worst, and based on chlorophyll- contained 10 g/L is called as eutrophic waters